Peripheral Nerve Regeneration Using Different Germ Layer-Derived Adult Stem Cells in the Past Decade - Yu Li; Yuzuru Kamei; Miki Kambe; Katsumi Ebisawa; Mayumi Oishi; Keisuke Takanari (Behavioural Neurology)
Peripheral nerve injuries (PNIs) are some of the most common types of traumatic lesions affecting the nervous system. Although the peripheral nervous system has a higher regenerative ability than the central nervous system, delayed treatment is associated with disturbances in both distal sensory and functional abilities. Over the past decades, adult stem cell-based therapies for peripheral nerve injuries have drawn attention from researchers. This is because various stem cells can promote regeneration after peripheral nerve injuries by differentiating into neural-line cells, secreting various neurotrophic factors, and regulating the activity of in situ Schwann cells (SCs). This article reviewed research from the past 10 years on the role of stem cells in the repair of PNIs. We concluded that adult stem cell-based therapies promote the regeneration of PNI in various ways.